2016
DOI: 10.1016/j.tube.2015.09.006
|View full text |Cite
|
Sign up to set email alerts
|

The looming tide of nontuberculous mycobacterial infections in Portugal and Brazil

Abstract: Nontuberculous mycobacteria (NTM) are widely disseminated in the environment and an emerging cause of infectious diseases worldwide. Their remarkable natural resistance to disinfectants and antibiotics and an ability to survive under low-nutrient conditions allows NTM to colonize and persist in man-made environments such as household and hospital water distribution systems. This overlap between human and NTM environments afforded new opportunities for human exposure, and for expression of their often neglected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 109 publications
0
20
0
Order By: Relevance
“…From 1991 to 1997 a study with 1,892 NTM isolates from 1,248 patients in the state of São Paulo, showed that MAC and M. kansasii were the most frequently species identified (12). Nunes-Costa et al (2016) reviewing the literature about NTM infections in Brazil and Portugal found that MAC was the most reported NTM in Brazilian studies (48%), followed by M. Kansasii (17%), M. fortuitum (7%), M. gordonae (6%), M. abscessus (5%) and M. chelonae (3%), quite similar to what is observed in Portugal (9). The findings of our study showed that M. intracellulare is the most frequent NTM isolated in pulmonary specimens from patients with confirmed NTM disease in Southern Brazil, followed by M. avium and M. abscessus.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…From 1991 to 1997 a study with 1,892 NTM isolates from 1,248 patients in the state of São Paulo, showed that MAC and M. kansasii were the most frequently species identified (12). Nunes-Costa et al (2016) reviewing the literature about NTM infections in Brazil and Portugal found that MAC was the most reported NTM in Brazilian studies (48%), followed by M. Kansasii (17%), M. fortuitum (7%), M. gordonae (6%), M. abscessus (5%) and M. chelonae (3%), quite similar to what is observed in Portugal (9). The findings of our study showed that M. intracellulare is the most frequent NTM isolated in pulmonary specimens from patients with confirmed NTM disease in Southern Brazil, followed by M. avium and M. abscessus.…”
Section: Discussionmentioning
confidence: 58%
“…Brazil is a continental country and NTM isolation rates are quite different among different regions, but there is a predominance of MAC, M. kansasii and M. fortuitum causing active NTM disease. Brazil is a high tuberculosis (TB) burden country and had for many years overshadowed the role of NTM in human disease (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…21,22 In addition to mycobacterial species that cause TB, there are several nontuberculous mycobacteria (NTM) that are an emerging health threat. 23,24 Mycobacterium marinum is an NTM and an opportunistic human pathogen and an established model for studying M. tb pathogenesis. 2529 A large-scale, shotgun proteogenomic approach aimed at improving genomic annotation reported NTA of proteins in the H37Rv laboratory strain of M. tb .…”
Section: Introductionmentioning
confidence: 99%
“…pig's wild boars, elephants, horse (M. silvaticum), and dog(M. hominissuis;Escobar-Escamilla et al, 2014;Nunes-Costa, Alarico, Dalcolmo, Correia-Neves, & Empadinhas, 2016;Yong et al, 2011).Therefore, there is the possibility of incidence of zoonotic and occupational infections by these subspecies.4 | OTHER MAC SUBSPECIESOther subspecies of MAC based on 16s rRNA sequencing mostly include M. chimaera (or MAC-A serovar from human respiratory system), M. colombiense (from children lymph nodes), M. arosiense (or MAC-X serovar from systemic osteomyelitis of HIV-infected children), M. indicus pranii (MIP or Mw), M. vulneris (isolated from ulcers), M. xenopi, and M. lepraemurium which caused infections less common in humans. Because of nonoptimization of diagnostic methods, these subspecies are underestimated…”
mentioning
confidence: 99%